Traumatic Hip Fracture and Primary Elective Total Hip Patients are Not the Same: A Comparison of Comorbidity Burden, Hospital Course, Postoperative Complications, and Cost of Care Analysis. Issue 11 (November 2020) - Lowe, Jason; Mitchell, Sean M.; Agarwal, Sumit; Jones, Clifford B.
Abstract : Objectives: To compare patient admission comorbidity profiles, length of stay, readmission rate, postoperative complications, mortality rate, and cost of care between acute geriatric hip fractures (HF) and elective total hip arthroplasties (THA). Methods: Retrospective cohort. Setting: Multicenter health care system. Patients: Eighteen thousand forty-two geriatric HF treated with operative fixation or arthroplasty and 8761 elective total hip patients were reviewed. Main Outcome Measurements: Charlson Comorbidity Index, length of stay, ICU admission, readmission rate, postoperative complications, mortality rates, and cost of care. Results: Medical comorbidities: chronic pulmonary disease, chronic kidney disease, coronary artery disease, heart failure, liver cirrhosis, and cerebrovascular disease were higher in HF patients as was mean Charlson Comorbidity Index ( P < 0.001). Albumin was lower and HgbA1c higher in HF patients ( P < 0.001). Average length of stay was 5.0 versus 2.6 days ( P < 0.001) with 8.5% of HF patients being managed in the ICU versus 1.8% of THA patients. Readmission rates for HF and THA patients were 21.4% and 6.2%, respectively ( P < 0.001). Minor and major complications were higher in the HF cohort ( P < 0.001), as were 30-day (1.97% vs. 0.17%) and 1-year mortality rates (3.49% vs. 0.40%) ( P < 0.001). Mean hospital cost of care was nearly 15, 000 US dollars more expensive in HF patients when compared to the elective THA cohort ( P < 0.001). Conclusions: HF patients have increased comorbidity burdens, lengths of stay, ICU admissions, readmission rates, complications, mortality, and costs of care than patients with elective total hip arthroplasty. In the era of pay for quality performance, health systems must reconcile the difference between these 2 patient cohorts. Level of Evidence: Prognostic Level III. See Instructions for Authors for a complete description of levels of evidence.